Environmental Toll of Colonial and Neocolonial Exploitation: An Postcolonial Ecocritical Study of Intizar Hussain’s Basti - Muhammad Afzal; Arhamna Azam; Shaina Iqbal (Dialogue Social Science Review (DSSR), 2025)
Colonial exploitation and environmental degradation are inherently interconnected, with colonial powers profoundly impacting the ecological health and sustainability of colonized territories, leading to significant disruptions in the natural balance. “The relationship between colonialism and environmental degradation is a complex and often overlooked aspect of our global ecological crisis” (Bhandikeri, 2024, para. 1). This research paper investigates environmental toll of colonial and neocolonial exploitation in Intizar Hussain’s Basti, using a postcolonial ecocritical framework. Basti critiques environmental consequences of imperialism and its neocolonial aftermath, exploring how these forces have altered the relationship between humans and nature. By tracing the disintegration of ecological harmony, the research paper highlights the cultural and environmental repercussions of historical and ongoing exploitations. The novel shows how colonial policies not only imposed tyranny on people but also set the environment ablaze with unsustainable practices. This research paper argues that the colonial and neocolonial forces exerted and continue to exert the main forces of environmental exploitation, and also that environmental awareness plays a great role in understanding the postcolonial state of affairs. It deploys sustainable development as a way to decolonize environmental practices by providing a critical insight into how imperial shadow still affects both people and environment.